Media Language in the Publication of Political and social Conflict - Zhumatayev, E. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
At the current stage of the policy pursued by the Head of State in full compliance and coordination of the internal and external policy of Kazakhstan, it is important to preserve interethnic harmony and to find a solution in any multinational country. Mass media publications also have an important role in establishing inter-ethnic or inter-ethnic relations. It is obvious that television and radio broadcasting and Internet media are the key tools in the development and promotion of this position as the main tool for the human being. This article considers the linguistic peculiarities of the texts which can be a source of interethnic clashes in the ethnic discourse published in these press releases.